Reflexivity and psychology - Marsico, Giuseppina; Ruggieri, Ruggero Andrisano; Salvatore, Sergio (YIS (Series), 2015)
Reflexivity is a category that is too appealing not to arouse interest. It is a concept largely diffused in several psychological domains, as well as associated with epistemological, theoretical, methodological and practical discussions. At the same time, it is a very polysemic notion, understood and used in many different ways.If one approaches the notion and tries to identify the semantic boundaries of its usage, the seeming solidity of the term fades away, and a rather liquid semantic field emerges - a field where several interpretations coexist, being contingent to the context of the discussion in which they are implemented. This is the reason that makes the notion of reflexivity a prototypical example of the difficulties encountered by Psychology - and more in general social sciences -in the effort to define their own language. The term "reflexivity" - like many others the language of Psychology is full of - is used in daily life and thus its semantics is shaped by the pragmatic, contingent functions it serves in such communicational circumstances. The apparent - from afar - clearness of the concept does not concern its conceptual, epistemic status, but the capacity of the sign to contribute efficaciously to mediate and regulate the exchange.The theoretical elaboration of the notion of reflexivity can be seen as one of the ways of performing the challenging task of developing an intentional language for Psychology. By working on such a notion one can realize that common sense lies at the core of psychological science and what it means to separate the former from the latter, so as to pursue the foundational task of developing Psychology as a theory-driven science.